Two new species of Acrodictys M.B. Ellis from India - D.K. AGARWAL; I.K. KUNWAR, C. MANOHARACHARY*, N.K. RAO, (Indian Phytopathology, 2006)
Two new species of Acrodictys are proposed, A. elliptica sp. novo with long conidiophores having elliptical conidia and darker central portion. The conidia in A. lignicola sp. novo are obclavate with apical appendages. These characters do not match with the other known species of Acrodictys.